Postpartum changes in plasma viral load and CD4 percentage among HIV-infected women from Latin American and Caribbean countries: the NISDI Perinatal Study - Victor H Melo; Jorge A Pinto; Laura Freimanis-Hance; Cesar Gutierrez; Mário Peixoto; Breno Santos; Daisy M Machado; Esaú C Joao; Kathleen Robergeau; Jennifer S Read (Memorias do Instituto Oswaldo Cruz, 2011)
The goal of this study was to evaluate changes in plasma human immunodeficiency virus (HIV) RNA concentration [viral load (VL)] and CD4+ percentage (CD4%) during 6-12 weeks postpartum (PP) among HIV-infected women and to assess differences according to the reason for receipt of antiretrovirals (ARVs) during pregnancy [prophylaxis (PR) vs. treatment (TR)]. Data from a prospective cohort of HIV-infected pregnant women (National Institute of Child Health and Human Development International Site Development Initiative Perinatal Study) were analyzed. Women experiencing their first pregnancy who received ARVs for PR (started during pregnancy, stopped PP) or for TR (initiated prior to pregnancy and/or continued PP) were included and were followed PP. Increases in plasma VL (> 0.5 log10) and decreases in CD4% (> 20% relative decrease in CD4%) between hospital discharge (HD) and PP were assessed. Of the 1,229 women enrolled, 1,119 met the inclusion criteria (PR: 601; TR: 518). At enrollment, 87% were asymptomatic. The median CD4% values were: HD [34% (PR); 25% (TR)] and PP [29% (PR); 24% (TR)]. The VL increases were 60% (PR) and 19% (TR) (p < 0.0001). The CD4% decreases were 36% (PR) and 18% (TR) (p < 0.0001). Women receiving PR were more likely to exhibit an increase in VL [adjusted odds ratio (AOR) 7.7 (95% CI: 5.5-10.9) and a CD4% decrease (AOR 2.3; 95% CI: 1.6-3.2). Women receiving PR are more likely to have VL increases and CD4% decreases compared to those receiving TR. The clinical implications of these VL and CD4% changes remain to be explored.